2004
DOI: 10.1002/ajim.10332
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium‐related work and cause‐specific mortality at the United States Department of Energy Hanford Site

Abstract: Workers employed in jobs with routine potential for plutonium exposure have low mortality rates compared to other Hanford workers even with adjustment for demographic, socioeconomic, and employment factors. This may be due, in part, to medical screening. Associations between duration of employment in jobs with routine potential for plutonium exposure and mortality may indicate occupational exposure effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…The strong confounding apparent from internal exposure category observed in analyses for brain tumors, radiogenic solid cancers, leukemia, lymphoma and multiple myeloma is consistent with other studies that have found lower mortality rates in nuclear workers who were monitored and exposed to plutonium and other radionuclides, likely because of strong selection effects for healthy, stable workers into this job category (Wing et al 2004). …”
Section: Radiation Dose-response Analysessupporting
confidence: 75%
See 2 more Smart Citations
“…The strong confounding apparent from internal exposure category observed in analyses for brain tumors, radiogenic solid cancers, leukemia, lymphoma and multiple myeloma is consistent with other studies that have found lower mortality rates in nuclear workers who were monitored and exposed to plutonium and other radionuclides, likely because of strong selection effects for healthy, stable workers into this job category (Wing et al 2004). …”
Section: Radiation Dose-response Analysessupporting
confidence: 75%
“…Nuclear worker studies have typically classified workers by status as of first (Gilbert et al 1992), longest-held (Wing et al 2004), or last (Beral et al 1985) job title. In the present study, the primary objective in evaluating SES was to consider it as a surrogate of potential behavioral factors such as smoking.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Hanford workers with routine potential for plutonium exposure have lower cancer rates than other workers, even after adjusting for SES, employment status, and in vivo monitoring status, 25 suggesting an internal healthy worker effect possibly related to the Hanford occupational medicine programme, which required additional medical screening for workers entering jobs involving special hazards. 37 However, lung cancer ERR/Sv values are 24.62 (6.76 to 59.02) for plutonium workers versus 7.02 (1.61 to 15.20) for other Hanford workers.…”
Section: Discussionmentioning
confidence: 99%
“…8 24 25 We used industrial process and work history records to create a job-exposure matrix for potential exposure to plutonium. 25 Workers were classified as potentially exposed to plutonium, starting on their first day of employment in a job with routine plutonium exposure potential.…”
Section: Methodsmentioning
confidence: 99%